Designing the Diversity of Canadian Libraries: Excerpts from the CARL Inclusion Perspectives Webinar by Racialized Library Colleagues - Cho, Allan; Bolefski, Afra; Tellis, Cecilia; Jin, Lei; Kumaran, Maha (Partnership, 2022)
Five academic librarians from libraries that represent the Canadian Academic Research Libraries (CARL) were invited to share their experiences as racialized librarians. In 2021, the Canadian Academic Research Libraries (CARL) hosted an Inclusion Perspectives Webinar Series, organized by CARL’s Equity, Diversity, and Inclusion Working Group (EDIWG) and the contents of this paper are presentations by these librarians who were invited to speak on systems, structures, and policies needed to dismantle racism; practical strategies to attract and retain racialized library employees; accreditation issues; and provide advice for what Canadian library leaders can start doing immediately.